Analisis Perspektif Mahasiswa Akuntansi dalam Penerapan Kertas Kerja ATLAS di Era Digital - Solissa, Ferdinando; Astuty, Putu Anggreyani Widya; Turot, Margaretha; Tagi, Marthen (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This research was conducted on students in the Accounting Study Program, Faculty of Economics and Business, Victory University, Sorong. The aim of this research is to analyze Accounting Students' Perspectives on the Application of ATLAS Working Papers in the Digital Era in the Accounting Study Program, Faculty of Economics and Business, Victory University, Sorong. This research can be used as a reference for those who will carry out research, namely knowledge related to Accounting Student Perspectives regarding Audit Tool and Linked Archive System (ATLAS) working papers. This research method is the approach used in this analysis is Critical Discourse Analysis (CDA) and Structural Discourse Analysis. Data was collected from in-depth interviews with students who have used ATLAS in their research, as well as from academic discussion forums. Based on the research results, respondents answered that ATLAS features in the application can be understood because they are assisted by lecturers and get references from YouTube regarding webinars and training. ATLAS app. Apart from that, the results of the research also show that respondents support that audits in implementing the ATLAS application must have the ability and learn the choice of words and language styles in the application features if they are in accordance with the case exercises that have been completed and given examples for input. Social interaction with applications plays an important role in enhancing students' learning experience and skill development. By utilizing technology to interact, students can create a more inclusive, collaborative and supportive learning environment.